Overview of Flow Cytometry and Microbiology. Issue 1 (16th April 2018) - Robinson, J. Paul
Abstract: Although in recent years flow cytometry has become commonplace in hematology and immunology laboratories, application of the technology to microbiology remains largely unrealized. This overview presents the historical background, discusses applications in various areas of the field, and speculates on the directions of future developments. The availability of high‐quality methods should be a prime factor in convincing microbiologists that flow cytometry may have certain advantages over traditional methods and that it does indeed have much to contribute to microbiology. © 2018 by John Wiley & Sons, Inc.